LOGOPEDIA SENSORYCZNA JAKO WSPARCIE ROZWOJU MOWY DZIECKA. STUDIUM INDYWIDUALNEGO PRZYPADKU - Serzysko-Zdanowska, Małgorzata (Student Niepełnosprawny. Szkice i Rozprawy, 2021)
The aim of this study is to present the connections between speech disorders and sensory integration processing and disorders in children’s functioning and suggestions of therapeutic activities. Sensory processing dysfunctions may affect the development of cognitive functions and speech. In this study I would like to emphasize the effectiveness of elements of the sensory integration therapy. Multisensory methods influence the sense of balance. They also shape the child’s motor skills, coordination, the ability to plan, and communicate at the same time, stimulating communication and general speech development.